2012
DOI: 10.1180/minmag.2012.076.8.41
|View full text |Cite
|
Sign up to set email alerts
|

Gas migration experiments in bentonite: implications for numerical modelling

Abstract: In the Swedish KBS-3 repository concept, there is potential for gas to be generated from corrosion of ferrous materials under anoxic conditions, combined with the radioactive decay of the waste and radiolysis of water. A full understanding of the probable behaviour of this gas phase within the engineered barrier system (EBS) is therefore required for performance assessment. We demonstrate key features from gas transport experiments on pre-compacted Mx80 bentonite, under laboratory and field conditions, and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 13 publications
3
18
0
1
Order By: Relevance
“…In addition, a number of mathematical models have been developed to simulate the gas transport processes observed through these laboratory and field-scale studies with some success [9][10][11][12]. However, no studies to date have been able to determine the exact mechanisms which control gas entry, flow, and pathway sealing [4,6,8,[13][14][15][16][17]. Development and use of numerical models are of key importance in understanding the processes involved and their use in long-term safety assessments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of mathematical models have been developed to simulate the gas transport processes observed through these laboratory and field-scale studies with some success [9][10][11][12]. However, no studies to date have been able to determine the exact mechanisms which control gas entry, flow, and pathway sealing [4,6,8,[13][14][15][16][17]. Development and use of numerical models are of key importance in understanding the processes involved and their use in long-term safety assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Field scale observations at an underground research facility in Sweden confirmed these results, showing clear hydromechanical coupling during gas flow (Harrington et al 2007;Cuss et al, 2010Graham et al, 2012).…”
Section: Evidence For Dilatancy Controlled Gas Flowmentioning
confidence: 86%
“…Finally, the persistence of a preferential pathway after their formation is a point that should be considered with caution, as some experiments have shown the instability of the pathways (e.g. Horseman 1999; Graham et al 2012). Here, it is simply considered that the pathway remains open once it is formed (the porosity and the permeability continue to follow the constitutive laws of the pathway dilation model).…”
Section: Discussionmentioning
confidence: 99%